Vitamilk Booster / Syarifah Salsabila Sayed Hassan - Sayed Hassan, Syarifah Salsabila (2021)
Business opportunities allows people to begin their own business that involves in many aspects such as sale, lease of any product, service, equipment and many more. Business opportunities are really related to the case study and business then apply it on our business plan in order to be a successful entrepreneur also how we identify any course of production of beginning until end. It also teaches us on how to solve the problem that occur in business by having a strategic plan. I have started my business for a month starting from 5th May 2021 as an agent for the product name Vitamillk Booster. I started from the ground and try to experience and learning so many things day by days as it can improve my business skill for the better future. The product that I have been sell is based on milk which is goat milk that contains a lot of benefit for body health also there many other ingredients that includes in that milk. It is obviously a beauty health product for people no matter what age or gender all of them can consume it in daily life. The product came with three variation of flavour which is Vanilla, Strawberry and Apple. This product includes so many fruit extracts such as pomegranate are one of those fruits. This product has their own speciality that can boost the consumer strength of the bones and many other benefits that are very useful to the body. This product came out in white and pink colour theme with a price RM55.00 for one bottle. The product also available for all country in Malaysia including Sabah and Sarawak which will be easy for any people out there who want to purchase this product but having difficulties. As a student that need to keep up with study, I should have a strategic plan about the business to make sure that there will be no problem that occur during the run of the business. This is very important to take a note about all the thing including cash flow, the quality of the product and many more that need to take it seriously. Having a motivation is the major attitude that need to be care of since I had faced with so many challenges thing and learning the experience thoroughly as I will gain more knowledge about business related day by days.